Peran Metode Mind Mapping Dalam Meningkatkan Hasil Belajar SKI di MTsN Kota Bogor - Hilda Handayani; Sri Nurul Milla; Sutisna sutisna (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Learning outcomes are very important in a person's education to determine a learning success that has been obtained after following the teaching and learning process. There are various teaching methods that can be used by teachers to obtain learning outcomes in students. One of them is the Mind Mapping method. Furthermore, this study aims to determine whether there is a role of the Mind Mapping method in improving the learning outcomes of SKI material on Khulafaurrasyidin in class VII students at MTsN Kota Bogor. The research method used is quantitative. Data collection using tests with multiple choice forms. The data analysis technique uses the T-Test Test. In this study there are several findings, namely 1). There was an increase from the Pre-Test results to the Post-Test results in the control class of 11.34. And the Pre-Test results and Post-Test results in the experimental class amounted to 16.94; 2). The average N-Gain Score in the experimental class was 57.0411 or 57.04%; 3). Independent sample t-test output in the Equal Variances Assumed section shows that the Sig value. (2 tailed) of 0.000 <0.05. Based on the above findings, it can be concluded that there is a significant difference in increasing the value of student learning outcomes, so that there is a Role of the Mind Mapping Method in improving SKI Learning Outcomes on Khulafaurrasyidin Material in Class VII Students at MTsN Kota Bogor. Keywords: Islamic Culture History; Learning Outcomes; Mind Mapping Method.